Cancer / Vol. 3 - 20160731 frey50; Buratovich, Michael A.; Jackson-Grusby, Laurie (Ipswich, MA Salem Press, 2013)
This invoves Volume 3 which inclues cancer biology, carcinogens and suspected carcingens, chemotherapy and other drugs, complementary and alternative therapies, lifestyle and prevention.
Volume I. Diseases, Symptoms and Conditions A-O -- Volume II. Diseases, Symptoms and Conditions P-Z, Medical Specialties, Organizations, Social and Personal Issues -- Volume III. Cancer Biology, Carcinogens and Suspected Carcinogens, Chemotherapy and Other Drugs, Complementary and Alternative Therapies, Lifestyle and Prevention -- Volume IV. Procedures, Appendixes, Index.
Editor, first edition, Jeffrey A. Knight, Mount Holyoke College.
Keywords: Cancer; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Cancer; Encyclopedia